Haploinsufficiency of the NOTCH1 Receptor as a Cause of Adams–Oliver Syndrome With Variable Cardiac Anomalies. (August 2015) - Southgate, Laura; Sukalo, Maja; Karountzos, Anastasios S.V.; Taylor, Edward J.; Collinson, Claire S.; Ruddy, Deborah; Snape, Katie M.; Dallapiccola, Bruno; Tolmie, John L.; Joss, Shelagh; Brancati, Francesco; Digilio, Maria Cristina; et al.
<x xml:space="preserve">Abstract</x> Background— Adams–Oliver syndrome (AOS) is a rare disorder characterized by congenital limb defects and scalp cutis aplasia. In a proportion of cases, notable cardiac involvement is also apparent. Despite recent advances in the understanding of the genetic basis of AOS, for the majority of affected subjects, the underlying molecular defect remains unresolved. This study aimed to identify novel genetic determinants of AOS. Methods and Results— Whole-exome sequencing was performed for 12 probands, each with a clinical diagnosis of AOS. Analyses led to the identification of novel heterozygous truncating NOTCH1 mutations (c.1649dupA and c.6049_6050delTC) in 2 kindreds in which AOS was segregating as an autosomal dominant trait. Screening a cohort of 52 unrelated AOS subjects, we detected 8 additional unique NOTCH1 mutations, including 3 de novo amino acid substitutions, all within the ligand-binding domain. Congenital heart anomalies were noted in 47% (8/17) of NOTCH1-positive probands and affected family members. In leukocyte-derived RNA from subjects harboring NOTCH1 extracellular domain mutations, we observed significant reduction of NOTCH1 expression, suggesting instability and degradation of mutant mRNA transcripts by the cellular machinery. Transient transfection of mutagenized NOTCH1 missense constructs also revealed significant reduction in gene expression. Mutant NOTCH1 expression was associated with downregulation of the Notch target genes HEY1 and HES1, indicating that NOTCH1-related AOS arises through dysregulation of the Notch signaling pathway. Conclusions— These findings highlight a key role for NOTCH1 across a range of developmental anomalies that include cardiac defects and implicate NOTCH1 haploinsufficiency as a likely molecular mechanism for this group of disorders.